2017
DOI: 10.1007/s10554-017-1293-x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of heart rate on coronary calcium scores: a multi-manufacturer phantom study

Abstract: To evaluate the influence of heart rate on coronary calcium scores (CCS) using a dynamic phantom on four high-end computed tomography (CT) systems from different manufacturers. Artificial coronary arteries were moved in an anthropomorphic chest phantom at linear velocities, corresponding to < 60, 60-75 and > 75 beats per minute (bpm). Data was acquired with routinely used clinical protocols for CCS on four high-end CT systems (CT1-CT4). CCS, quantified as Agatston and mass scores were compared to reference sco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 24 publications
5
32
0
Order By: Relevance
“…Prospective ECG triggering is used in patients with low and stable heart rates (< 60 bpm). This technique assumes that the interval between two R waves remains stable for the entire duration of the acquisition (van der Werf et al 2018 ). Modern CT scanners also provide the option to skip an acquisition in prospective ECG triggering mode if an extra systole occurs.…”
Section: Introductionmentioning
confidence: 99%
“…Prospective ECG triggering is used in patients with low and stable heart rates (< 60 bpm). This technique assumes that the interval between two R waves remains stable for the entire duration of the acquisition (van der Werf et al 2018 ). Modern CT scanners also provide the option to skip an acquisition in prospective ECG triggering mode if an extra systole occurs.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that plaque classification also depends on the density and size, where relatively small and soft calcified plaques may remain undetected [32]. Van der Werf et al found that at an increased heart rate, the Agatston scores of low-density calcified plaques were similar to the reference scores but that the Agatston scores of medium-and high-density calcified plaques were increased by up to 50% [11]. In our study, all CNN architectures gained the highest classification accuracy for plaques with low density.…”
Section: Discussionmentioning
confidence: 99%
“…Whether using ECG-triggered cardiac or non-triggered chest scans, an accompanied limitation is the presence of motion artifacts, which considerably decreases the accuracy of CAC detection and quantification [11]. To decrease the motion artifacts in ECG-triggered CT, the temporal resolution should be shorter than 10% of one cardiac cycle time [12].…”
Section: Introductionmentioning
confidence: 99%
“… 21 Electrocardiography trigger output was used to ensure that acquisition was done during linear motion of the calcifications. 13 …”
Section: Methodsmentioning
confidence: 99%
“… 10 , 11 , 12 Moreover, CAC scores can vary greatly due to motion of the coronary arteries during the scan phase of a CAC scoring CT acquisition. 13 In order to study these differences, their possible impact on clinical outcome, and to optimize acquisition protocols, dedicated coronary calcium phantoms are frequently used. In the well‐established international standard developed for CAC quantification by McCollough and colleagues, a commonly evaluated commercially available anthropomorphic phantom was used (thorax and CCI phantom, QRM, Möhrendorf, Germany).…”
Section: Introductionmentioning
confidence: 99%